2017
DOI: 10.1038/s41598-017-11104-4
|View full text |Cite
|
Sign up to set email alerts
|

RERT: A Novel Regression Tree Approach to Predict Extrauterine Disease in Endometrial Carcinoma Patients

Abstract: Some aspects of endometrial cancer (EC) preoperative work-up are still controversial, and debatable are the roles played by lymphadenectomy and radical surgery. Proper preoperative EC staging can help design a tailored surgical treatment, and this study aims to propose a new algorithm able to predict extrauterine disease diffusion. 293 EC patients were consecutively enrolled, and age, BMI, children’s number, menopausal status, contraception, hormone replacement therapy, hypertension, histological grading, clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…In the present investigation, we demonstrated for the first time that high sHE4 levels are correlated with aggressive tumor characteristics and worse prognosis in UCC patients. Clinical evidence has confirmed the role of sHE4 as a biomarker with diagnostic and prognostic value in gynecological malignancies, mostly in ovarian and endometrial carcinoma ( 10 – 15 ). In particular, high sHE4 levels have been correlated with poor clinical outcome, as an independent prognostic factor.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In the present investigation, we demonstrated for the first time that high sHE4 levels are correlated with aggressive tumor characteristics and worse prognosis in UCC patients. Clinical evidence has confirmed the role of sHE4 as a biomarker with diagnostic and prognostic value in gynecological malignancies, mostly in ovarian and endometrial carcinoma ( 10 – 15 ). In particular, high sHE4 levels have been correlated with poor clinical outcome, as an independent prognostic factor.…”
Section: Discussionmentioning
confidence: 87%
“…Among recently reported serum biomarkers in gynecological cancer, one of the most promising is the Human Epididymis Protein 4 (HE4 or WFDC2), a member of the whey acidic protein (WAP) four-disulfide core gene cluster bearing a conserved motif found in several protease inhibitors ( 8 ). HE4 was first described by Kirchhoff et al ( 9 ) in human epididymal tissue and was subsequently found expressed in many other normal tissues, particularly of the reproductive tracts and of the central respiratory airways, as well as in gynecological malignancies, where HE4 has probably shown the most promising clinical results for early diagnosis and prognosis ( 10 – 15 ). Conversely, data regarding its role in UCC are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…https://thejns.org/doi/abs/10.3171/2020.9.FOCUS20681 KEYWORDS pandemic; anxiety; machine learning Three different models were used to identify which variables (X) have the greatest impact on the outcomes (Y). Because the variables were of a different nature (qualitative and quantitative), mostly asymmetrical, and related to Y by nonlinear relationships, a machine learning approach was chosen: the random forest (RF), 24 which is an ensemble method [25][26][27] that combines thousands of regression trees. 28 The idea behind the RF is quite simple: first, the algorithm perturbs the data set, generating many bootstrap samples and growing, on each of them, an overfitted decision tree (i.e., each terminal node contains few observations).…”
Section: (In Detail Between Stai-y1 [State] and Stai-y2 [Trait] Scormentioning
confidence: 99%
“…To estimate the BS-EWM, the outcome (Alive/Dead) was modeled using as covariates: (i) Brescia X-ray score, (ii) 17 analytes, (iii) age. Since most of the covariates analyzed were strongly correlated (multicollinearity) (Figure S1) and their relationships with the outcome were non-linear, the BS-EWM was estimated using Random Forests (Breiman, 2001) (Carpita and Vezzoli, 2012), a non-parametric machine-learning method (Vezzoli, 2011) (Vezzoli et al, 2017). Moreover, the algorithm is able to manage missing values which are common in clinical studies.…”
Section: Methodsmentioning
confidence: 99%